A Thematic and Content Analysis of Instructional and Rehearsal Procedures of Preschool Social Emotional Learning Programs. Issue 3 (September 2017) - White, Antoinette; Moore, Dennis William; Fleer, Marilyn; Anderson, Angelika
RESEARCH HAS DOCUMENTED THE positive effects of social emotional learning (SEL), and educational policy developments and accepted learning standards are beginning to reflect these findings. However, how best to include evidence-based practices in the instruction of social emotional competencies in regular preschool settings is not yet fully understood. Through a thematic and content analysis, this study identifies the target skills, implementation, instructional and rehearsal procedures in eight effective preschool SEL programs. The analysis describes a differential relationship between target skills and instructional and rehearsal procedures. The findings highlight the relevance of particular procedures in the instruction of specific competencies, and in broader social emotional instruction. These findings may assist educators in instructional planning with current learning documents, such as the Early Years Learning Framework (DEEWR, 2009).